Potential therapeutic targets in plasma cell disorders: a flow cytometry study - Kriegsmann, Katharina; Schönland, Stefan; Hegenbart, Ute; Wallenwein, Katrin; Braun, Ute; Mai, Elias K.; Hillengaß, Jens; Goldschmidt, Hartmut; Jauch, Anna; Ho, Anthony Dick; Raab, Marc-Steffen; Hundemer, Michael (Cytometry. Part B, Clinical cytometry, 2017)
Cytometry Part B: Clinical Cytometry focuses on the development and applications of cellular system analysis and array based technologies as applied to clinical practice and translational research. This journal also covers relevant techniques such as flow cytometry, image cytometry, beadbased and slide-based array analyses, as well as other cell-based spectroscopic analyses. In addition, Clinical Cytometry publishes clinical and translational investigations that identify and validate the features and molecules important in diagnosis, prognosis, and therapeutic management of patients
First published: 15 December 2015
Gesehen am 15.10.2018